Effect of Training on Patient Self‐Assessment of Joint Counts in Rheumatoid Arthritis: A Systematic Review. Issue 12 (17th September 2021) - Tam, Keith; Hazlewood, Glen S.; Barber, Claire E. H.
Abstract : Objective: Patient self‐assessed joint counts, if accurate and reliable, could potentially serve as a useful clinical assessment tool in rheumatoid arthritis (RA). This systematic review examines the effect of patient training on the inter‐rater reliability of joint counts between patients and clinicians. Methods: The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. A search was performed in PubMed, Embase, Cochrane Library, and CINAHL for articles that incorporated patient training and measured the reliability of patient self‐assessed joint counts in RA. Articles were included if they reported on the inter‐rater reliability between patient and clinician joint counts in both trained and untrained patients with RA. Data were extracted on characteristics of patients, structure and components of the training interventions, joint count reliability of patients with and without training, and patient feedback on training interventions. The relevant data were summarized and described. Results: Multiple training methods have been studied (n = 5), including in‐person sessions run by rheumatologists and instructional videos on the joint examination. Overall, training improved the reliability of patient self–joint counts, with more marked improvement in reliability of swollen joint counts than tender joint counts. Patients had positive feedback when surveyed on their experiences with training. Conclusion: Various training modalities (in‐person and video‐based) may be effective at improving reliability of patient self–joint counts. More research is needed on this topic, with potential areas for future research including 1) comparison between the efficacy of different modalities of training, and 2) impact of patient factors (education level and disease severity) on the efficacy of training.